The impact of the Reading and Mathematics Project on the Teaching Practices of the first three grades Teachers from the point of view of teachers - Al-Omari, Khaled M. (Dirasat: Educational Sciences, 2020)
This study aimed to reveal the impact of the reading and numeracy initiative on the teaching practices of the first three grade teachers from the point of view of teachers. To achieve the goal of the study, the researcher developed a questionnaire to collect data and consisted of (42) paragraphs distributed over four areas: planning for the class share, presentation of teaching content, means, methods and activities, and assessment skills. Its sample consisted of (210) teachers, who completed the course of the reading and calculation initiative. Their results showed that teachers had affected their classroom practices due to the reading and numeracy initiative at an average rate for the tool as a whole and also for its four areas. The results also showed that there are no significant differences at the level of indication (0.05) except on the experience variable and in favor of those with experience in the category of more than 5 years to less than 10 years. The study recommended the importance of developing a follow-up plan for teachers by the Ministry of education aimed at determining the extent of their application of the skills they have acquired, and identifying the various obstacles that limit their ability to apply within the actual reality of teachers so that they can be overcome in the future.